2017
DOI: 10.1140/epje/i2017-11545-1
|View full text |Cite
|
Sign up to set email alerts
|

Preferential hydration fully controls the renaturation dynamics of collagen in water-glycerol solvents

Abstract: Glycerol is one of the additives which stabilize collagen, as well as globular proteins, against thermally induced denaturation -an effect explained by preferential hydration, i.e. by the formation, in water/glycerol solvents, of a hydration layer whose entropic cost favors the more compact triplehelix native structure against the denatured one, gelatin. Quenching gelatin solutions promotes renaturation which, however, remains incomplete, as the formation of a gel network gives rise to growing topological cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Combined experimental results and theoretical solutionscattering simulations yielded direct evidence on the effect of glycerol on the hydration (solvation) shell of myoglobin and the thermal structural transition. These results clearly indicate that the function of glycerol as a stabilizer of proteins is related to the preservation of protein hydration by the preferential exclusion of glycerol from the hydrationshell region of the protein at glycerol concentrations lower than $40% v/v, which agrees well with previous studies using different techniques (1)(2)(3)(4)(5)(6). At glycerol concentrations above $50% v/v, the partial penetration or replacement of glycerol into or with the hydration shell of water molecules surrounding the protein surface appears to depend on the glycerol concentration.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…Combined experimental results and theoretical solutionscattering simulations yielded direct evidence on the effect of glycerol on the hydration (solvation) shell of myoglobin and the thermal structural transition. These results clearly indicate that the function of glycerol as a stabilizer of proteins is related to the preservation of protein hydration by the preferential exclusion of glycerol from the hydrationshell region of the protein at glycerol concentrations lower than $40% v/v, which agrees well with previous studies using different techniques (1)(2)(3)(4)(5)(6). At glycerol concentrations above $50% v/v, the partial penetration or replacement of glycerol into or with the hydration shell of water molecules surrounding the protein surface appears to depend on the glycerol concentration.…”
Section: Introductionsupporting
confidence: 91%
“…In the second model, glycerol molecules are preferentially excluded from the protein surface because of the hydration repulsion force. In this case, the hydration-shell density that is always higher than in bulk water is preserved and has a constant value even with increased glycerol (preferential exclusion model and preferential hydration model (1,6)). Although the above models are extreme cases induced by cosolutes depending on physicochemical conditions, it is meaningful to elucidate qualitatively typical effects of cosolutes on the scattering curve of protein.…”
Section: Simulation Of X-ray Scattering Curve and Radius Of Gyration Of Myoglobin In Molecular-crowding Solution Based On The Preferentiamentioning
confidence: 95%
See 1 more Smart Citation
“…By the combination of experimental results and theoretical solution scattering simulations, we have obtained a direct structural evidence on the effect of glycerol on the hydration-shell of myoglobin and the initial process of amyloid transition of myoglobin induced by temperature variation. The present results clearly indicate that the function of glycerol as a stabilizer of proteins is related to the preservation of protein hydration by the preferential exclusion of glycerol from the hydration-shell region of the protein at low glycerol-concentration (≤ ~40 % v/v), which agree well with the previous studies using different techniques [1][2][3][4][5][6]. The results at high glycerol-concentration (≥ ~50 % v/v), suggests the appearance of the preferential solvation (partial preferential penetration or replacement of glycerol into or with hydration-shell water surrounding the protein surface).…”
Section: Introductionsupporting
confidence: 93%
“…The Ramman and quasi-elastic inelastic neutron scattering study of the effect of glycerol on lysozyme showed that the protein's fast conformational fluctuations and low-frequency vibrations and its temperature variations are very sensitive to behavior of the solvents [5]. The recent rheometer study on the effect of glycerol on the dynamics of collagen re(de)naturation suggests the presence of a nanometer thick, glycerol-free hydration layer where glycerol is fully expelled out of it [6]. In spite of many previous studies, there are fewer direct evidence showing the effect of glycerol on the protein structure, its preferential hydration layer and thermal stability.…”
Section: Introductionmentioning
confidence: 99%